MANAJEMEN MULTIKULTURAL DALAM BERPOLITIK - Khairiah Khairiah (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: The purpose of this paper is to describe multicultural management in politics. The method used is descriptive qualitative approach. The component that becomes the benchmark is impact analysis, due to politics in the lives of multicultural communities in Indonesia, as a basis for providing opinions or conclusions about a process and system of political activities in cultural diversity in multicultural societies in order to maintain the integrity of the Unitary Republic of Indonesia (NKRI), Pancasila, The 1945 Constitution and Unity in Diversity. This article discusses multicultural management programs in politics. The results show that multicultural management as a management of outlook on life can realize political awareness. With multiculturalism, it can give birth to views and a healthy political system, so as to create a sense of security, comfort and peace in the life of the nation and state, so the author can suggest if you want the political conditions to take place safely, peacefully and harmoniously, then enhance multicultural management in society. Keywords: Multicultural; Management; Politics